2012
DOI: 10.1542/peds.2011-1589
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Brief Intervention, and Referral for Alcohol Use in Adolescents: A Systematic Review

Abstract: Based on existing evidence, it is not clear whether SBIRT is an effective approach to risky alcohol use among adolescent patients in acute care. Additional research is needed around interventions and implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 40 publications
2
68
0
Order By: Relevance
“…Numerous systematic reviews have been published on ASBI in younger adolescents in recent years 37,[72][73][74][75][76][77][78][79] (details given in Appendix 2). Jackson et al's review 37 of ASBI for young people in health settings identified eight controlled trials 53,[80][81][82][83][84][85] for young people.…”
Section: Primary and Secondary Prevention Interventions For Risky Drimentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous systematic reviews have been published on ASBI in younger adolescents in recent years 37,[72][73][74][75][76][77][78][79] (details given in Appendix 2). Jackson et al's review 37 of ASBI for young people in health settings identified eight controlled trials 53,[80][81][82][83][84][85] for young people.…”
Section: Primary and Secondary Prevention Interventions For Risky Drimentioning
confidence: 99%
“…53,80,[82][83][84][85][87][88][89][90][91]93 Nine of the included studies 83,84,[87][88][89][90][91][92][93] related to young people aged ≥ 18 years and included a heterogeneous range of interventions from very brief MI to four group sessions of 30-40 minutes, which meant that generalisability BACKGROUND TO THE RESEARCH NIHR Journals Library www.journalslibrary.nihr.ac.uk could not be ascertained. A review of the literature by Yuma-Guerrero et al 78 around BI in emergency departments in the USA for young people identified seven randomised controlled trials (RCTs). [82][83][84][85][95][96][97] The primary studies included young people aged 12-20 years.…”
Section: Primary and Secondary Prevention Interventions For Risky Drimentioning
confidence: 99%
“…Associations between alcohol consumption and earlier onset of drinking and negative consequences of drinking (as measured by the ESPAD questions) and poorer health and functioning were also observed. This study found ED waiting rooms a source of willing research participants, and this context may also represent a teachable moment to change young people's behavior using either face-to-face or electronic interventions [31,37,38]. The ED also has a high level of staff expertise who are well placed to initiate safeguarding procedures where required and who provide a good point of onward referral to specialist services.…”
Section: Discussionmentioning
confidence: 85%
“…Previous research has demonstrated the immediate postinjury time is an ideal time to capitalize on a teachable moment with preventive interventions. 28,78 Previous ED screening, brief intervention, and referral to treatment approaches have focused on substance use, [79][80][81] with a recent study showing positive findings for intervening for both substance use and youth violence among younger less violence-involved youth. 45,82 Interventions for hospitalized assault-injured youth have shown promise linking hospitalized youth with community-level resources.…”
Section: Discussionmentioning
confidence: 99%